2016
DOI: 10.1108/ijpdlm-12-2015-0300
|View full text |Cite
|
Sign up to set email alerts
|

Supplier development for sustainability: contextual barriers in global supply chains

Abstract: Purpose -The purpose of this paper is to explore contextual barriers to supplier development for sustainability (SDS) in global supply chains and managerial remedies to mitigate such barriers. Design/methodology/approach -A dyadic case study design was adopted with a Western European buyer and six of its Chinese suppliers. The database consists of 41 interviews and 81 documents. Findings -Contextual barriers to SDS in global supply chains derive from complexities in the sustainability concept, socio-economic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(111 citation statements)
references
References 75 publications
1
110
0
Order By: Relevance
“…For instance, scholars have examined drivers, barriers, and performance outcomes of green supply chain management (Luthra, Garg, & Haleem, 2015;Scur & Barbosa, 2017), green manufacturing (Ghazilla et al, 2015), and green innovations (Abdullah, Zailani, Iranmanesh, & Jayaraman, 2016). In a similar vein, other studies have explored environmental issues in purchasing and supply management such as green purchasing (Kaur, Sidhu, Awasthi, Chauhan, & Goyal, 2018), green supply management (Lintukangas, Kähkönen, & Tuppura, 2014), and green supplier development (Busse, Schleper, Niu, & Wagner, 2016), thus providing detailed insights about environmental and economic supply chain issues but neglecting a holistic focus on all SSCM dimensions (Panigrahi et al, 2018).…”
Section: Drivers For and Barriers To Sscm Implementationmentioning
confidence: 99%
“…For instance, scholars have examined drivers, barriers, and performance outcomes of green supply chain management (Luthra, Garg, & Haleem, 2015;Scur & Barbosa, 2017), green manufacturing (Ghazilla et al, 2015), and green innovations (Abdullah, Zailani, Iranmanesh, & Jayaraman, 2016). In a similar vein, other studies have explored environmental issues in purchasing and supply management such as green purchasing (Kaur, Sidhu, Awasthi, Chauhan, & Goyal, 2018), green supply management (Lintukangas, Kähkönen, & Tuppura, 2014), and green supplier development (Busse, Schleper, Niu, & Wagner, 2016), thus providing detailed insights about environmental and economic supply chain issues but neglecting a holistic focus on all SSCM dimensions (Panigrahi et al, 2018).…”
Section: Drivers For and Barriers To Sscm Implementationmentioning
confidence: 99%
“…It also helps in saving the possible costs to be incurred in the future for controlling the damages [43]. From idea generation to designing products that use fewer materials, low energy, and reduce harmful emissions, these can have significant economic and environmental effects on their results [44,45].…”
Section: Sscm Practicesmentioning
confidence: 99%
“…The network theory provides an insight for travel agents (buyers) in the downstream to analyze the integrating mechanism of social capital derived from tour suppliers (sellers) in the upstream of the TSC network. Zhang and Zhang (2018) pointed out that the networking of small tourism enterprises (STEs) is crucial to both their business operations and regional development [2], and tourists, neighbors, other STEs, and government were treated as major stakeholders in a social network by them. Following this logic, in this paper we concentrated on the travel agent (TA) extended network we designed (among focal travel agents, tour associations, research institutions, and OTA (Online Travel Agency) platforms) to explore the structure of collaborative relationships and to further analyze the influential relationship between a travel agent's positional embeddedness and the sustainable integration of tour suppliers by exposing the asymmetric interdependency among actors in the TA extended network.…”
Section: Tsc Networkmentioning
confidence: 99%
“…Apart from purchasing services from various suppliers, Travel agents have more of an emphasis on collaborating with outer tour suppliers to exchange resources, mainly through technical means (e.g., system integrating) and commercial means (e.g., price discounts) to achieve sustainable relationships with them, in order to reduce the transactional costs and improve the agility of TSC. Busse et al (2016) found that supplier development for sustainability (SDS) is useful for buyers to shape the supply pool to mitigate potential supply chain sustainability risks [38]. Among the existing literature, some scholars have also researched two-party relationships from the marketing perspective.…”
Section: Understanding Of Tour Supplier Integration (Tsi)mentioning
confidence: 99%
See 1 more Smart Citation